Strukturalno-pomenska analiza pridige kot žanra - Bizjak Končar, Aleksandra (Slavistična revija, 2005)
Genre analysis, supported by detailed textual examples from a morphologically tagged textual corpus, sheds light on the complicated question of the structural construction of the text. To describe textual meaning the author created a semantic network, which underscores the relationship between the entity and the event on the one hand and between the subject and the predicate on the other. She recorded the linguistic features un the linear flow of the text, which would be difficult to keep track of by manual tagging, with the automated part-of-speech tagger for Slovene development at the Inštitut za slovenski jezik at ZRC SAZU.
Keywords: oblikoslovje; pridige; Slovene; slovenščina; tekstna lingvistika; žanri